Review of visualization techniques for landslide and flood disaster data - Yussof S.; Husin N.B.; Ibrahim Z.; Din M.M.; Ghapar A.A.; Din N.M.; Abdullah F. (Maxwell Science Publications, 2023)
The aim of this study is to review the data visualization techniques that have been used for landslide and flood research. Landslide and flood are two of the natural disasters that commonly occur in Malaysia. Due to the large amount of damage that both landslide and flood can cause, it is important for researchers to predict where and when these two disasters will occur and the extent of damage that can happen. Data visualization techniques have been used by researchers in both areas to facilitate them in making a better prediction. However, data visualization techniques are used differently in the two areas. In landslide research, the visualizations techniques are used to visualize monitored landslide data. In flood research, the visualization techniques are used to visualize the predicted impact of flood, where they are used as a component in a flood simulation system. In both cases, data visualization technique has not been used to its full potential and this opens up a door for further research opportunities with regard to using data visualization to improve our prediction on landslide and flood occurrence. Maxwell Scientific Organization, 2015.